FUZZY DELPHI METHOD (FDM) FOR DEVELOPING COMPONENTS OF THE CLASSROOM ACTIVITY-BASED INSTRUCTIONAL DESIGN (CAID) MODEL IN TEACHING CHINESE AS A FOREIGN LANGUAGE - Liu Lifei; Mohd. Ridhuan Mohd Jamil; Nadzimah Idris (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Activity-based teaching has emerged as a key strategy in advancing quality education and classroom activities play a crucial role in teaching Chinese as a foreign language (TCFL). However, the proficiency of TCFL teachers in the activity-based teaching is currently insufficient and unable to meet the demands of TCFL teaching activities. The objective of this study is to design and develop a Classroom Activity-Based Instructional Design (CAID) model that will support teachers in implementing activity-based teaching methods. Using Design and Development Research (DDR) approach, the study involved expert consensus through literature reviews and semi-structured interviews with five experts. The Fuzzy Delphi Method (FDM) was used for model validation with 19 experts, confirming that the model components met all criteria. As a result, consensus was reached on the CAID model components, which were universally accepted by experts.